The Current Status of Percutaneous Coronary Intervention in Korea: Based on Year 2014 Cohort of Korean Percutaneous Coronary Intervention (K-PCI) Registry - Jang, Jae-Sik; Han, Kyoo-Rok; Moon, Keon-Woong; Jeon, Dong Woon; Shin, Dong-Ho; Kim, Jung-Sun; Park, Duk-Woo; Kang, Hyun-Jae; Kim, Juhan; Bae, Jang-Whan; Hur, Seung-Ho; Kim, Byung Ok; et al. (Korean circulation journal, 2017)
Although several multicenter registries have evaluated percutaneous coronary intervention (PCI) procedures in Korea, those databases have been limited by non-standardized data collection and lack of uniform reporting methods. We aimed to collect and report data from a standardized database to analyze PCI procedures throughout the country. Both clinical and procedural data, as well as clinical outcomes data during hospital stay, were collected based on case report forms that used a standard set of 54 data elements. This report is based on 2014 Korean PCI registry cohort data. A total of 92 hospitals offered data on 44967 PCI procedures. The median age was 66.0 interquartile range 57.0-74.0 years, and 70.3% were men. Thirty-eight percent of patients presented with acute myocardial infarction and one-third of all PCI procedures were performed in an urgent or emergency setting. Non-invasive stress tests were performed in 13.9% of cases, while coronary computed tomography angiography was used in 13.7% of cases prior to PCI. Radial artery access was used in 56.1% of all PCI procedures. Devices that used PCI included drug-eluting stent, plain old balloon angioplasty, drug-eluting balloon, and bare-metal stent (around 91%, 19%, 6%, and 1% of all procedures, respectively). The incidences of in-hospital death, non-fatal myocardial infarction, and stroke were 2.3%, 1.6%, and 0.2%, respectively. These data may provide an overview of the current PCI practices and in-hospital outcomes in Korea and could be used as a foundation for developing treatment guidelines and nationwide clinical research.